Controllable waveguide via dielectric cylinder covered with graphene: Tunable entanglement. (1st August 2016) - Zeng, Xiaodong; Liao, Zeyang; Al-Amri, M.; Suhail Zubairy, M.
Abstract: The dielectric cylinder covered with graphene (DCCG) is found to be a promising platform for studying multi-qubit collective effects. The plasmons supported by DCCG have huge wave numbers and low loss. Under some conditions, the zeroth- and first-order modes even have the same wavelength. Qubits along DCCG can interact with each other strongly by coupling with the plasmons within tens to hundreds of plasmonic wavelengths. Additionally, the electro-optical tunability of graphene means that we can manipulate the plasmonic wavelength and subsequently the dynamic evolutions of the qubits mediated by the DCCG conveniently. These properties make the graphene be a potential choice for quantum information device.